Effectiveness of Audio Visual Therapy in Reducing Anxiety and Pain in Children During Medical Procedures: Review Literature - Oki Setyawati; Haryati Purwandari; Kuat Widodo (GLOBAL HEALTH SCIENCE GROUP, 2026)
Children often experience anxiety and fear when undergoing medical procedures. Audiovisual educational media can be used as a distraction and an educational tool to reduce this problem. To review the empirical evidence on the development and effectiveness of audiovisuals in reducing children pain, and anxiety during medical procedures. This is a review literature and retrieved articles from PubMed, Scopus, ScienceDirect, and Wiley databases published between 2020 and 2025. A total of 8,077 articles were initially identified through the database search using keywords audiovisual OR Virtual reality AND paediatric OR children AND anxiety. The study selection process was conducted following the PRISMA flow diagram, which involved screening, eligibility assessment, and removal of duplicates. The 8 articles were reviewed using JBI RCT appraisal tool and showed moderate to high quality. The selection followed the PRISMA diagram, with thematic analysis applied for data synthesis. The audiovisual media is proven effective as a non-pharmacological intervention to reduce anxiety, pain, and increase positive behaviour of children when undergoing medical procedures. Audiovisual have rule to distract children from pain and effect on the reducing anxiety including increase positive behaviour during procedures.